Design and construction of a rapid filter of multiple bed to pilot scale - León, Orietta; Cárdenas, Carmen; Carruyo, Jenny (Rev. Téc. Fac. Ing. Univ. Zulia)
A rapid filter on a pilot scale was designed and constructed, based in the prototype of one of the filters from the filtration train in stalled on a treatment dehydration plant of oilfield water. The parameters that were considered to design the filter are: diameter and porosity of the filter environment and depth of the bed prototype. The empirical relation considered between the maximum size of the grain and diameter of the filter was 1:50.